Nickel complexes of a bis(benzimidazolin-2-ylidene)pyridine pincer ligand with four- and five-coordinate geometries - Brown, David; Skelton, B. (The Royal Society of Chemistry, 2011)
The four- and five-coordinate complexes [(CNC)NiX2] (X = Cl, Br, I), [(CNC)NiX]PF6 (X = Cl,Br) and [(CNC)NiCl]ClH2O have been isolated, where CNC is the bis(N-butylbenzimidazolin-2-ylidene)-2,6-pyridine pincer ligand. A five-coordinate geometry is rare for this class of complex.Where amenable, the complexes have been structurally characterised by single crystal X-raydiffraction studies and in solution by NMR, UV-vis and MS studies. The five-coordinate dibromocomplex [(CNC)NiBr2] is readily prepared on the gram-scale from the benzimidazolium saltprecursor and Ni(OAc)24H2O in DMSO without the exclusion of air. Halide exchange and saltmetathesis reactions using [(CNC)NiBr2] afford the other four- and five-coordinate complexes.[(CNC)NiBr2] displays very low solubility, and upon dissolution affords solutions of the fourcoordinate[(CNC)NiBr]+. Factors that influence the formation of four- or five-coordinatecomplexes with this ligand class are discussed.